The development of a design and development framework between OEM and supplier - Ogundana, Damilola (Cranfield University, 2019)
Suppliers are of great importance to OEMs because of the benefits that can be gained from collaborating with them. But for the OEM to select the appropriate supplier for the specific job they want accomplish, they must first create criteria that can be used to evaluate the supplier. The purpose of this thesis is to develop a design and development framework between OEM and supplier. The framework is focused only on the design and development activities and not manufacturing. This research was able to identify the right criteria for OEMs to use to assess, select and evaluate suppliers. Moreover, it was able to clarify the difference in criteria for each of the three aforementioned activities. The construction of the framework commenced with the use of an extensive literature review which was followed by an industrial field study consisting of 5 interviews with four companies who specialise in different sectors of engineering. The outcomes were integrated to generate the contents of the supply chain framework. A case study was simulated in order to verify the framework. The design and development framework provides the necessary means by which an OEM can assess, select and evaluate suppliers during product design and development processes. As a result of this, a functionally feasible and enhanced design and is more efficient can be realised. The framework that was developed as a result of this is very comprehensive and is able to mitigate the challenges faced in the industry today, regarding a outsourcing of OEMs’ product development activities to supplier. The contributions to the knowledge are as follows: (1) The developed framework provides a clear understanding of what constitutes as assessment criteria, selection criteria and evaluation criteria in product design and development within the supply chain. (2) The framework mitigates the evolving challenges faced by OEM and suppliers when product design and development is outsourced. (3) The developed framework encompasses all the activities involved in assessing, selecting and evaluating suppliers throughout the outsourcing process.